A cost-effective analysis of intrapartum care for low risk mothers at two different levels of care in Jeli, Kelantan. - Ibrahim, Wan Norlida
A study of the cost-effectiveness of intrapartum care for the low risk antenatal mother was undertaken at two different levels of care in Kelantan. Cases were selected from J eli alternative birthing center (ABC) (community-based center) and the respective{ district hospital, Tanah Merah Hospital (hospital-based center) for one year startingfrom 1st January until 31 st December 2001. Cost analysis was conducted from provider and patient perspectives. The research team used effective intrapartum care as the outcome measure. The criteria for the effective intrapartum care are based on normal clinical outcome and maternal satisfaction. A total of 117 low risk antenatal mother were recruited in the study, 58 and 59 low risk antenatal mothers from community-based and hospital-based center respectively. Results: The marginal means of provider cost, patient cost and societal cost differed significantly (p<0.001) between Jeli ABC and Tanah Merah hospital for intrapartum care of low risk antenatal mother. The marginal mean provider costs were RM 390.55 and RM 521.93 per case for Jeli ABC and Tanah Merah hospital respectively. The marginal mean patient costs were RM110.32 and RM256.81 per case for ABC Jeli and Tanah Merah hospital respectively. The marginal mean societal costs were RM541 .59 and RM per case for ABC intrapartum care and Tanah Merah hospital respectively. Jeli ABC was five times more effective (OR 5.17, CI: 2.010,13.304). The cost-effectiveness ratios ofRM138.00 and RM323.90 per unit outcome for Jeli ABC and Tanah Merah hospital respectively were significantly different (p<0.001). Conclusion: The study found that Jeli alternative birthing center level (community-based center) is less expensive than Tanah Merah hospital (hospital-based center) in providing intrapartum care for low risk mothers. The center also has a better clinical outcome and higher satisfaction than Tanab Merah hospital therefore Jeli ABC is more effective in providing intrapartum care for low risk mother than Tanah Merah hospital. Jeli ABC is also more cost-effectiveness compared to Tanah Merah hospital.